Assessment of concentrations and distribution of radionuclides and non-radionuclides elements in Manjung coastal water area / Anisa Abdullah - Abdullah, Anisa (2017)
Rapid socioeconomic development in Manjung area may contribute to the pollution of the Manjung coastal water area. One of the main causes of marine pollution is the uncontrolled release of pollutants such as radionuclide and non-radionuclide elements mainly from anthropogenic activities. Unfortunately, the pollutants transported to the atmosphere and deposited back over the land or run off to the river and flow into coastal water area and finally enter the food chain. They have potential radiological and health risk to human body. Therefore, this study is focused on assessment of radionuclide (4°K, 238U and 232Th) and non-radionuclide (Hg, Cd, Cr, Cu, Pb, As, Se, Fe and Zn) in water, sediment and rp.arine biota from Manjung coastal water area. The measurements were cai:ied out using Energy Dispersive X-Ray Fluorescence (EDXRF) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Linkages between seawater-sediment-marine biota potential acts as indicator of pollution level and health risk to the human population of the study area. As results, the pollution trends as revealed by Enrichment factor (EF), Geo-accumulation index (Igeo) and Pollution index (PI) of the radionuclides and non-radionuclides elements in marine sediment were found corresponding to the river sediment concentration level signified that the pollution originated from the Bekah River. The elements of 4°K, Hg, Fe and Cu are in the category of low pollution level, while elements Cr, Zn, 238U, Pb and 232Th in the category of medium pollution level, whereas ·elements Cd, As and Se in the category of high pollution level. Based on Principle Component Analysis (PCA) and Cluster Analysis (CA), the possible sources of radionuclides and non-radionuclides elements are attributed from agricultural, industrial and domestic activities. The possible radiology and the chemical toxic effect of the radionuclides and non-radionuclides elements in seawater and marine sediment could exert the negative effect to the biota and human those consume the biota. Therefore, significant high risk was found for consumption of marine biota due to high concentration of elements 232Th, Cr, As and Pb but the risk depends on intake rate per day and the species of biota consumed. Hence, it is important to carried out regular monitoring of pollution level in Manjung coastal water area in order to provide information radiological and health risk assessment for human population in the study area.